KONSEP AMANAH DALAM AL-QUR’AN - Ah. Haris Fahrudi (Universitas Kiai Abdullah Faqih Gresik, 2023)
Abstract: Among the major problems faced by humans today is the loss of security in various lines of life, both in the individual, family, and community. Among the reasons for the loss of security and peace in this life is the fading of trust in man. The Qur'an as a book of divine instruction has given its guidance on the importance of trust, to whom it is handed over and how it should be carried out in order to create security and peace in life. This study discusses descriptively interpretively how the Qur'anic concept regarding the concept of amanah in the Qur'an and its relationship with security and peace by examining verses about amanah with a maudlui interpretation approach. This research resulted in the conclusion that the word amanah in the Qur'an has a number of meanings that are closely related to security. The Qur'an affirms that amanah is a natural thing for humans, is universal, and covers all lines of life, both religious affairs, on individuals and social life, such as in the fields of science and information, social, economic, political and power. The establishment of trust guarantees the creation of security and peace and the loss of trust creates insecurity and insecurity in every line of life. Keyword: amanah, safe, Tafsir maudlu’i